If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -1 = 11 + -1n Reorder the terms: -1 + n = 11 + -1n Solving -1 + n = 11 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. -1 + n + n = 11 + -1n + n Combine like terms: n + n = 2n -1 + 2n = 11 + -1n + n Combine like terms: -1n + n = 0 -1 + 2n = 11 + 0 -1 + 2n = 11 Add '1' to each side of the equation. -1 + 1 + 2n = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 2n = 11 + 1 2n = 11 + 1 Combine like terms: 11 + 1 = 12 2n = 12 Divide each side by '2'. n = 6 Simplifying n = 6
| 33*26-33*22=33*(-22) | | 4(t+p)-3=6+-13 | | .25x+.5=.5 | | 5=14v-9v | | 2(k-3)=3(k-4) | | 101=x+3x+(x+4) | | -3x-1=-37 | | 45m=120 | | 8x(x+2)=0 | | 10x-2x-15=27+3x | | 4(w+9)=20 | | 12g^2+16g-3=0 | | 6+m=21 | | 9v^2-55v+50=0 | | a=bcW+x-y | | 11-3-2x+3x=4x-4 | | 7x-58=2x-8 | | (5x)-6-7x=2 | | 6x+(x-16)=180 | | 10+50m=110 | | 0.33+2=6x-73 | | -55.2=6.9c | | 4(4x+6)=2(8x+12) | | 2(6c+8)=4+6c | | 26=b-16 | | 3t^2-9t=12 | | 50+10m=110 | | V=(3.14)(2*2)(150) | | (3x^5)-2=0 | | 2(5x-1)+5x-1+3x=78 | | 1.4+t=0 | | 20+8m=92 |